A Phase 3 Efficacy and Safety Study of Ravulizumab in Adult Patients With Neuromyelitis Optica Spectrum Disorder: Study Design and Methodology. (5th December 2022) - Pittock, Sean; Allen, Kerstin; Mashhoon, Yasmin; Yountz, Marcus
Abstract : Objective: To present the design and rationale for the phase 3 trial ALXN-1210-NMO-307 (NCT04201262). Background: Eculizumab is a complement component 5 (C5) inhibitor approved for adults with anti-aquaporin-4 antibody-positive (AQP4+) neuromyelitis optica spectrum disorder (NMOSD). Ravulizumab, which binds the same C5 epitope, has a longer half-life with an extended dosing interval (every 8 vs every 2 weeks). We designed an innovative trial without concurrent placebo exposure to assess the efficacy and safety of ravulizumab in adults with AQP4+ NMOSD. Design/Methods: NA. Results: ALXN1210-NMO-307 is an open-label, multicenter, single-arm study using the placebo group from the PREVENT trial as a comparator. Constancy with PREVENT is maintained, including similar patient populations, adjudication procedures, and endpoints. Sensitivity analyses are prespecified to account for differences in patient characteristics. To measure confounding, an E-value is calculated for the primary endpoint (time-to-first adjudicated on-trial relapse). Given the serious impact of NMOSD attacks, eculizumab approval precluded the use of a concurrent comparator for ethical reasons, as it would require assigning patients to placebo when effective treatments exist. A non-inferiority efficacy trial was also considered but recruiting the very large sample size to adequately power the study was not feasible for this ultra-rare disease. Thus, a standard randomized clinical trial design was used. The trial enrolled 58 adults with EDSS score = 7 to receive an infusion of ravulizumab every 8 weeks after the loading dose. The primary treatment period will end when the last enrolled patient reaches week 50 unless a predefined number of patients have an adjudicated on-trial relapse by that time. The entire treatment period will last up to ∼4.5 years. Conclusions: ALXN1210-NMO-307 is an ongoing study evaluating the efficacy and safety of ravulizumab in patients with AQP4+ NMOSD. It is designed to be consistent with PREVENT, and robust statistical methods will address the potential impact of an external comparator.